Realized pollen flow and wildling establishment from a genetically modified eucalypt field trial in Southeastern Brazil - Silva, Paulo H.M. da [UNESP]; Sebbenn, Alexandre M. [UNESP]; Grattapaglia, Dario; Conti, José Luiz F. (Elsevier, 2017)
Confined field trials of genetically modified (GM) trees are the essential step toward the identification of the most productive cultivars and the assessment of the likely environmental impacts of the GM trees including the potential for gene flow by pollen and distance dispersal by seeds. Our study investigated the potential for wildling establishment and realized pollen flow from a clonal GM eucalypt field trial in Southeastern Brazil. The GM eucalypt stand was established in 2009, surrounded by a 3 m wide forest road and signal grass (Bracharia sp.) fields. No seedling regeneration was found between 2010 and 2014 in and around the stand, confirming the expectations of the unlikelihood of eucalypt seedling establishment based on its limited invasive potential in competitive tropical environments. In 2014, open-pollinated seeds were collected from 28 non-GM eucalypts located between three and 650 m distance from the GM trial. A total of 420 seedlings were grown in a greenhouse and screened for the presence of the transgenic construct by a multiplexed PCR assay targeting two transgenes and an internal control. The highest average transgene pollen flow (16%) was seen at short distances (3–15 m), rapidly diminishing to 3% by a 240 m distance and continued at this low rate up to the furthest distance assessed (650 m) from the GM trial. The negative exponential distribution of GM pollination success was similar to that observed in non-GM eucalypt pollen flow studies, indicating that low levels of effective pollination are expected over long distances. To the best of our knowledge, this is the first experimental assessments of realized pollen flow measured by the effective production of seedlings from a genetically modified tree in field conditions.
Keywords: Buffer zones; Genetically modified (GM) tree; GM pollen flow; GM wildling establishment